Opportunities for strengthening agriculture insurance programs: PCIC and LGU partnerships - Celia M. Reyes; Adrian D. Agbon; Christian D. Mina; Reneli Ann B. Gloria (Philippine Institute for Development Studies (PIDS), 2017)
Providing agricultural insurance to farmers and fisherfolk in the Philippines has been implemented for nearly three decades. While it is agreed that agricultural insurance is crucial in assisting farmers, fisherfolk, and governments in lessening the negative financial impact of natural events, issues of providing premium subsidies and being tied to credit in the Philippines remain to be important policy issues. This paper reviews available information about partnerships between local government units (LGUs) and the Philippine Crop Insurance Corporation. The aim is to look at these innovations that may promote and enhance agricultural insurance in the Philippines. Providing for full premium subsidies and as a form of loan to the farmers was implemented by the LGUs reviewed in this paper. Further study is needed to determine which scheme works best in terms of increasing coverage over the long term and ensuring financial viability.
Keywords: 330; agricultural insurance; LGUs; Philippine Crop Insurance; subsidy